PENDIDIKAN KARAKTER KELUARGA DI ERA DIGITAL - Tantin Puspita Rini; Moh Masduki (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2020)
In the digital era where everything can be obtained instantly and with high technology. In the future, the generation called millennial generation will be born. This generation has a habit of reading but low readability. They prefer to play on gadgets, internet and social media. This millennial generation has characteristics such as being connected to social media, sticking to their life's gadgets with gadgets, the internet has become one in their daily lives, hedonic, aware of their lifestyle, in terms of choosing a career they usually look for light workers but have a large income. Millennia needs to be strengthened in terms of character education. So that the existence of this generation can bring progress to the Indonesian nation. Submitting to formal educational institutions alone should not solve the problem This paper intends to examine the important role of the family in instilling noble values ​​in children so that noble characters are formed in the midst of the swift currents of change in this digital era, with a focus on the question of how important the role of the family is in instilling character. in children in the middle of the digital era. This research is a library research. The data collection technique in this research is also by examining various sources of literature such as books, magazines and other written sources. The results and data findings in the literature will later be analyzed and synthesized to be used as new ideas as a form of research results. Through parental assistance to children when using gadgets, it can certainly increase the role of the family in educating children in the digital era. Because of course we hope that current technological advances can benefit children both to improve their thinking skills and mental formation of children. It is also hoped that the government will be more proactive in giving emphasis so that parents do not neglect children's rights which are oriented towards mental development. This is needed so that children are more resilient in facing the extraordinary wind of information. Apart from being needed digital literacy in children and of course also for parents.